Upaya Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa dengan Menggunakan Model Discovery Learning - Anna Sari Rambe; Risna Mira Bella Saragih; Jihan Hidayah Putri (Departement of Mathematics Education, 2024)
The ability to understand mathematical concepts is the central part that leads to mastery of other mathematical concepts. There are still many students who cannot use concepts because they think mathematics is very difficult. This is why understanding concepts is prioritized over memorizing formulas. Students succeed in understanding mathematical concepts due to various things, one of which is caused by teachers who contribute and influence learning activities regarding students' understanding of mathematical concepts. The Discovery learning model is a learning theory which is defined as a learning process that occurs when students are not presented with lessons in their final form, but are expected to organize them themselves. Based on the results of individual assessment tests during the learning process, there was an increase from diagnostic tests, namely 50% to 69.23% in cycle I, and increased to 88.46% in cycle II. This proves that indirectly the use of the Discovery learning learning model in the material on systems of linear equations in two variables (SPLDV) has increased quite significantly.